Treatment of ulcers in traumatic injuries in children with gauze impregnated with chlorhexidine gluconate 2% - Nendika Dyah Ayu Murika Sari; Putri Kusuma Wardani Mahendra (Journal of Holistic Nursing Science, 2023)
Background: The basement membrane of the labial mucosa in children has a thin, delicate structure and is prone to trauma. Trauma can cause hyperemia, edema, epithelial desquamation, erosion, or ulceration, depending on the duration and intensity of the injury. Treatments to reduce pain in ulcers include the use of mouthwash and topical drugs such as corticosteroids, anesthetics, anti-inflammatories, and chlorhexidine gluconate. The aim of this paper is to report on the use of 2% Chlorhexidine gluconate gauze as a treatment for ulcers in children caused by traumatic injuries. Case Report: A 5-year-old girl came with her mother with complaints of swollen lips, pain, and a fussy child. Based on the results of the alloanamnesis, it was known that two days ago the child fell and hit the floor while playing at school. The objective examination revealed the presence of multiple yellowish-brown ulcers measuring about 5 mm on the superior and inferior labial mucosa, with brown crusted edges and edema. The treatment in this case is to apply gauze moistened with 2% chlorhexidine gluconate twice a day. Result of the Treatment: Seven days after treatment, the wound was completely healed. Conclusion: Treatment of labial mucosal ulcers in traumatic injuries can be done by applying gauze moistened with 2% chlorhexidine gluconate.